PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBASIS PEMBELAJARAN ABAD 21 DALAM MENINGKATKAN KETERAMPILAN MENULIS SISWA DI KABUPATEN GOWA - Nurhaedah Nurhaedah; Supriadi Supriadi; Satriani Satriani (ALGAZALI INTERNATIONAL JOURNAL EDUCATIONAL RESEARCH, 2020)
Abstract: Application of Project Based Learning Learning Model Based on 21st Century Learning in Improving Students' Writing Skills in Gowa Regency. This study aims to describe the application of the 21st century learning-based project based learning model in improving students' writing skills in Gowa Regency. This study used a Classroom Action Research (PTK) design. This research was conducted at SDN Sungguminasa II Kab. Gowa. There are 26 grade IV students consisting of 13 female students and 13 male students. The research time was carried out for four weeks. This research procedure was carried out through a classroom action research design consisting of cycle I and cycle II. The data collection techniques used in this classroom action research are as follows: Observation, Tests, and Documentation. The data analysis technique in this study was obtained by analyzing and managing data. Data analysis in this study was carried out by classifying teacher and student aspects. The technique used is qualitative and quantitative data analysis techniques. Furthermore, determining the indicators of success in research include process and outcome indicators. The results showed that the Project Based Learning model was effectively used to improve learning outcomes for writing at SD Gowa Regency. This is evidenced by the average value of student learning outcomes in the first cycle of 60.8% in the low category with a maximum value of 70, while the minimum score is 50. The number of students who did not complete was 19 out of 26 students. There was an increase in cycle II with the average value of student learning outcomes of 100% with a maximum value of 85, while the minimum score was 70 and all students achieved complete completion of the total number of students.Keywords: Project Based Learning, 21st Century, Writing